Morphometrics and structural changes of “Terung Asam” Sarawak (Solanum lasiocarpum Dunal) during growth and development - Albert Ting, Koon Soon; Phebe, Ding; Ramaiya, Shiamala Devi (Penerbit Universiti Sains Malaysia, 2023)
“Terung asam” Sarawak (Solanum lasiocarpum Dunal) is an underutilised fruit vegetable. Information on the fruit growth is very lacking. Thus, this study was conducted to characterise fruit growth pattern based on physical characters and cellular structures. Data were recorded weekly from fruit set until senescence. All the morphological growth of “terung asam” fruit exhibits a single sigmoid growth pattern that fitted well to logistic model. There are three distinct phases of growth, i.e., S1, S2 and S3. At S1, the size of fruit cells was small without intercellular spaces. As fruit grew to S2, cell size increased with distinct vascular tissues. By S3, fruit has achieved its maximum size with green peel turn to yellow and finally golden yellow at late S3. Cuticle and two types of trichomes formed the outer layer of fruit. The thickness of fruit exocarp increased while density of trichomes decreased as fruit developed.